Pengembangan Buku Ajar Biologi Berbasis STEM education-PjBL pada Materi Plantae - Trio Ageng Prayitno; Nuril Hidayati; Noventianus Umbu Ranja Uma (Jurnal Biologi dan Pembelajarannya (JB&P), 2024)
STEM education (Science, Technology, Engineering, and Mathematics) based textbooks and Project Based Learning (PjBL) learning models have never been developed by school educators. STEM education-PjBL can provide meaningful learning for students in understanding concepts and exploring through project activities. The aim of the research is to produce a biology textbook based on STEM education-PjBL on Plantae material that meets valid criteria. This type of research is development research and uses the Thiagarajan 4D development model consisting of define, design, develop, and disseminate. However, this research is limited to the develop stage. The research instruments used were a needs analysis questionnaire, a material expert validation questionnaire, and a learning media expert validation questionnaire. The results of the research show that the STEM education-PjBL-based biology textbook on Plantae material is declared very valid and appropriate in terms of material (91%) and learning media (99%). This STEM education-PjBL based biology textbook can be recommended as a learning resource in biology learning and a reference for teachers and other researchers if they want to develop a book by integrating learning approaches and models where the learning approach or model is integrated with the subject matter.